Kaum Awam Sebagai Misionaris Ad Gentes - Sudhiarsa, Raymundus I Made (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2014)
Lay people have always been protagonists in the life of the Church since the time of the apostles. They have also always been missionaries at the borders by the grace and call of Baptism and Confirmation. The arena of their missionary work is vast and complex which covers politics, economics, industry, education, the media, science, technology, the arts and sport, etc. In so-doing they have a great opportunity to encounter all kinds of people of every rank and way of life. It is, therefore, the responsibility of the Hierarchy to empower them with all kinds of religious means and to facilitate the fulfillment of their religious needs. The article also argues that lay Christians are partners of clergy and religious in missio ad gentes.